Experimental investigations of the magnetic asymmetry effect in capacitively coupled radio frequency plasmas. (25th October 2018) - Oberberg, M; Kallähn, J; Awakowicz, P; Schulze, J
Abstract: The electrical asymmetry effect allows control of the discharge symmetry, the DC self-bias, and charged particle energy distribution functions electrically by driving a capacitive radio frequency discharge with multiple consecutive harmonics with fixed, but adjustable relative phases. Recently, Trieschmann et al (2013 J. Phys. D: Appl. Phys. 46 084016) and Yang et al (2017 Plasma Process. Polym. 14 1700087; 2018 Plasma Sources Sci. Technol. 27 035008) computationally predicted that the discharge symmetry can also be controlled magnetically via the magnetic asymmetry effect (MAE). By particle-in-cell simulations they demonstrated that a magnetic field, that is parallel to the electrodes and inhomogeneous in the direction perpendicular to the electrodes, induces a discharge asymmetry due to different ion densities adjacent to both electrodes. This, in turn, is predicted to lead to the generation of a DC self-bias as a function of the difference of the magnetic field at both electrodes. In this way the MAE should allow control of the mean ion energy at both electrodes as a function of the magnetic field configuration. Here, we present the first experimental investigation of the MAE. In a low pressure discharge operated in argon at 13.56 MHz, we use a magnetron-like magnetic field configuration at the powered electrode, which leads to an inhomogeneous profile of the magnetic field perpendicular to the electrodes. By measuring the DC self-bias and the ion flux-energy distribution function at the grounded electrode as a function of the magnetic field strength at the powered electrode, the driving voltage amplitude and the neutral gas pressure we experimentally verify the concept of the MAE and demonstrate this technology to be a powerful method to control the discharge symmetry and process relevant energy distribution functions.